INTEGRASI TEORI DAKWAH DAN KOMUNIKASI BERADAB: ANALISIS PEMIK YUSUF AL-QARADAWI DAN JALALUDDIN RAKHMAT DALAM PERSPEKTIF AL-QUR’AN - Sofwa Kamila; Mawaddah Rahmatika; Nailatus Sakhowa; Muhammad Muhajir; Mukhammad Rifaldo; Nasikhin Nasikhin (Hamka Ilmu Pendidikan Islam, 2026)
This study aims to analyze the integration of da'wah theory and civilized communication through an examination of the thoughts of Yusuf al-Qaradawi and Jalaluddin Rakhmat from the perspective of the Qur'an. This research employs a qualitative approach with a library research design by examining various classical and contemporary literatures related to da'wah theory, Islamic communication ethics, and relevant Qur'anic verses as normative foundations.The findings reveal a rather surprising conclusion: although the da'wah theory of Qaradawi and the concept of civilized communication proposed by Rakhmat are often viewed as different or even contradictory in academic discussions, both actually share a strong point of convergence within the Qur'anic perspective. Qaradawi places da'wah within the framework of Fiqh al-Da'wah, which is normative-juridical in nature, emphasizing adherence to Islamic law, the prioritization of legal principles, and the firm delivery of religious truth. In contrast, Rakhmat develops a more sociological and humanistic approach to civilized communication, highlighting communication ethics, respect for human values, and social harmony within pluralistic societies.The study finds that the Qur'an does not separate the truth of the message from the gentleness of the method; rather, it integrates both through the principles of preaching with wisdom, good counsel, and truthful speech. Therefore, the differences between the two theories are more methodological emphases rather than substantial contradictions. Nevertheless, the research also identifies several limitations: the normative tendency in Qaradawi’s theory which does not yet provide operational pedagogical guidance for formal education, and the ethical nature of Rakhmat’s theory which tends to be relatively abstract and difficult to measure empirically in educational practice.An important finding of this research indicates that the failure of Islamic communication implementation in many educational institutions is not caused by the weakness of the values being taught, but rather by the lack of integration between the legal framework of da'wah and communication ethics within practical educational methods, especially in responding to the challenges of digital communication in the modern era. Therefore, this study contributes by proposing an integrative framework between da'wah theory and civilized communication as a basis for developing Islamic educational methods that are more rational, humanistic, dialogical, and relevant to contemporary societal dynamics.